Efficient Sustained-Release Nanoparticle Delivery System Protects Nigral Neurons in a Toxin Model of Parkinson's Disease - Qun Wang; Rui Ma; Piaoxue Liu; Guowang Cheng; Qi Yang; Xiaojia Chen; Zhenfeng Wu; Dongsheng Yuan; Tongkai Chen (MDPI AG, 2022)
Parkinson's disease (PD) is a serious neurodegenerative disease wherein the progressive destruction of dopaminergic neurons results in a series of related movement disorders. Effective oral delivery of anti-Parkinson's drugs is challenging owing to the blood-brain barrier (BBB) and the limited plasma exposure. However, polymeric nanoparticles possess great potential to enhance oral bioavailability, thus improving drug accumulation within the brain. In this work, biodegradable poly(ethylene glycol)-b-poly(trimethylene carbonate) (PEG-PTMC) nanoparticles (PPNPs) were developed to deliver Ginkgolide B (GB) as a potent treatment for PD, aiming to enhance its accumulation within both the blood and the brain. The resultant GB-PPNPs were able to facilitate sustained GB release for 48 h and to protect against 1-methyl-4-phenylpyridine (MPP+)-induced neuronal cytotoxicity without causing any toxic damage. Subsequent pharmacokinetic studies revealed that GB-PPNPs accumulated at significantly higher concentrations in the plasma and brain relative to free GB. Oral GB-PPNP treatment was also linked to desirable outcomes in an animal model of PD, as evidenced by improvements in locomotor activity, levels of dopamine and its metabolites, and tyrosine hydroxylase activity. Together, these data suggest that PPNPs may represent promising tools for the effective remediation of PD and other central nervous system disorders.